(untitled) (The International Journal for Scientific Research, 2026)
This study aimed to bridge the explanatory deficit in family business literature by formulating an innovative conceptual framework that integrates the "institutional asset lock" as an independent fourth force alongside the traditional forces of family, ownership, and management. It establishes the mechanisms of wealth survival and predicts structural failure points using a mathematical minimum function derived from the non-compensatory "weakest link" logic. Furthermore, it introduces a governance typology of global waqf (endowment) and trust models, focusing on strategic separation mechanisms between ownership control and executive management to ensure the multigenerational sustainability of these enterprises amidst a knowledge-based, digital economy. To achieve these objectives, the study adopts a constructive deductive methodology to build theoretical frameworks and advance the classic three-circle model. It employs a causal-explanatory approach, moving away from prescriptive-descriptive narratives, while relying exclusively on a comprehensive review and critical analysis of rigorous secondary academic sources—including peer-reviewed journal articles and international books—to deconstruct the legal mechanisms governing asset locks and compare them with contemporary waqf structures. The study yields several key findings, most notably proving that family business sustainability does not follow an additive logic; managerial excellence or financial abundance cannot compensate for the absence of an institutional asset lock. Additionally, it demonstrates the strategic efficiency of the "endowment without owners" model in protecting investment decisions and reducing interpersonal conflict costs through the absolute separation of control and management. It also conceptualizes the universal dimension of commercial waqf as the oldest model of its kind, structurally aligning it with major sustainable industrial foundations and trusts in Northern Europe and America to protect critical mass capital from demographic fragmentation. Based on these insights, the study offers a set of practical recommendations, primarily urging large family business owners to adopt the Family Enterprise Sustainability Index ( ), guiding them to move past soft, non-binding solutions like oral constitutions in favor of a legally binding institutional architecture that insulates the firm’s corporate personality. Finally, it calls upon policymakers and legislators to develop legal environments that accommodate commercial endowments, thereby ensuring investment governance flexibility for trustees and protecting productive assets from the risks of judicial liquidation and fragmentation.